The Digital Collateral Substitute: Modelling Supply Chain Finance (SCF) as a Catalyst for MSME Quality Standardization and Stable Sourcing in the Hotel F&B Supply Chain - Putranto, Diyan; Halawa, Fransiscus Amonio; Widodo, Rintis Eko; Setiawan, Fahmi; Ajizi, Budi Nurhamdani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the structural imperative for the Indonesian hotel industry to integrate localized MSMEs to mitigate high archipelagic logistics costs (22%–23.5% of GDP) by addressing the critical barrier of capital access required for quality. Employing a theoretical framework that integrates the Resource-Based View (RBV) and Transaction Cost Economics (TCE), we model how financial liquidity (SCF) translates into quantifiable operational excellence (Anon. Hotel SCM, 2023). A Quantitative Empirical Design utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to analyze data from 185 matched Buyer-Supplier dyads in the Java-Bali hotel F&B supply. Findings reveal substantial explanatory power for Sourcing Stability (R2 = 0.556) and confirm that SCF adoption significantly leads to MSME investment in Quality Standardization (H1), which in turn strongly improves Sourcing Stability (H3). Crucially, Fintech Development (the use of transparent digital platforms) acts as a significant positive moderator (H2 and H4), empirically validating the core theoretical contribution: verifiable transaction data effectively mitigates credit risk, functioning as a Digital Collateral Substitute that overcomes Information Asymmetry, unlocks greater capital access, and maximizes the stability outcomes of quality investment. This research provides a strategic blueprint for the hospitality sector to stabilize local supply chains, reduce high national inventory costs, and achieve national mandates for inclusive economic growth.